2020
DOI: 10.1002/ana.25909
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Risk of Relapse in Children and Adults with Myelin Oligodendrocyte Glycoprotein Antibody–Associated Disease

Abstract: Objective The main objective was to compare clinical features, disease course, and myelin oligodendrocyte glycoprotein (MOG) antibody (Ab) dynamics between children and adults with MOG‐Ab–associated disease (MOGAD). Methods This retrospective multicentric, national study included 98 children and 268 adults with MOGAD between January 2014 and September 2019. Cox regression model for recurrent time‐to‐event data and Kaplan–Meier curves for time to antibody negativity were performed for the objectives. Results Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
171
7
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(223 citation statements)
references
References 29 publications
19
171
7
5
Order By: Relevance
“…In this case, the combined SARS-CoV-2 and HHV6 infection likely triggered immune-mediated myelitis. This was confirmed by the positivity of MOG-IgG, an antibody linked to monophasic or recurrent demyelinating disorders including acute disseminated encephalomyelitis, optic neuritis, and transverse myelitis ( Cobo-Calvo et al, 2020 ). MOG-IgG-related demyelination can be post-viral or idiopathic.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In this case, the combined SARS-CoV-2 and HHV6 infection likely triggered immune-mediated myelitis. This was confirmed by the positivity of MOG-IgG, an antibody linked to monophasic or recurrent demyelinating disorders including acute disseminated encephalomyelitis, optic neuritis, and transverse myelitis ( Cobo-Calvo et al, 2020 ). MOG-IgG-related demyelination can be post-viral or idiopathic.…”
Section: Discussionmentioning
confidence: 84%
“…Demyelinating antibodies like MOG-IgG and AQP4-IgG should be tested in the setting of a suspicious clinical picture, such as longitudinally extensive myelitis or severe optic neuritis. MOG-IgG should then be repeated as persistent positivity may predict recurrent disease while transient positivity usually indicates a monophasic course ( Cobo-Calvo et al, 2020 ). This case expands the spectrum of autoimmune and infectious neurological complications of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was supported by several multicenter studies showing that isolated ON is often the first presentation of MOGAD. 5 , 12 Moreover, in a large multicenter retrospective study comparing the clinical features and visual outcomes between Caucasian and Asian MOG-IgG + ON patients, the authors found that Asian patients were less likely to have non-ON demyelinating manifestations. 6 This finding was comparable to findings in our study, in which all patients in the MOG-IgG + ON group were Asian.…”
Section: Discussionmentioning
confidence: 99%
“…Cobo‐Calvo et al 92 recently reported on the relapse risk in 336 cases of children and adults with MOGAD. Adults were at higher risk of relapse and had worse functional outcomes compared to children.…”
Section: Maintenance Therapiesmentioning
confidence: 99%